STUDY OF THE IMPORTANT ECONOMIC TRAITS OF SOYBEAN VARIETIES PLANTED AS A RECIPROCAL CROP - Kholikova M. A. (Web of Journals Publishing, 2024)
This article provides information about valuable economic characteristics of soybean varieties planted as repeated crops in Navoi region.
Keywords: soybean, local, foreign, valuable, legume, grain, productivity.